Risk Management and Risk Disclosure in a Period of Financial Crisis - Stylianou, Natasia (2009)
The purpose of this dissertation is to examine the extent to which companies disclose adequate and appropriate risk information within their annual reports, in order to communicate their risk management policies and practices to the external users of their annual reports. A sample of nine companies was selected, from three heterogeneous industries, all listed on the London Stock Exchange (LSE). The annual reports for a three year period (2006 through to 2008 inclusive) were studied for these nine companies, and the examination of their risk and risk management disclosures was conducted using content analysis, and more specifically, measured as the number of pages. An overall increase has been observed in the amount of risk-related information being disclosed within annual reports over the period under consideration, as a result of both regulatory factors and the need for more reporting due to the adverse effects of the current financial crisis on companies’ businesses. A positive association was found between the number of risk disclosures and the following variables: number of executive board directors, company size, capital structure, qualitative risk disclosures, future risk disclosures, good risk disclosures, and dual/multiple stock exchange listings. However, the amount and quality of risk management and/or risk disclosure were not found to be supported by the employment of a chief risk officer (CRO) or a risk committee, or even the appointment of independent non-executive board directors. Further, industry differences were negatively related to the amount of annual report risk disclosures.